Experiential brand loyalty: Towards an extended conceptualisation of consumer allegiance to brands. (September 2020) - Obiegbu, Chinedu James; Larsen, Gretchen; Ellis, Nick
This article synthesises the experiential and meaning-based dimensions of loyalty to extend the brand loyalty canon. The experientially loyal consumer is defined as one who is sufficiently invested in a brand to find personal symbolic meanings in the act of consuming that brand and engage around these meanings, individually or within the context of communities of similarly engaged consumers in the pursuit of identity projects. Drawing on a particular type of consumer that epitomises experiential loyalty – the fan, the features of this new conceptualisation are highlighted. The foundations of 'experiential brand loyalty' in consumer research are identified and examined. The concept of experiential brand loyalty is articulated and set alongside existing research as a complementary position that bridges the gap between brand loyalty and experiential consumption literatures. Implications are drawn for future research and marketing practice.